2014
DOI: 10.1016/j.ejphar.2014.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Novel mixed NOP/MOP agonist BU08070 alleviates pain and inhibits gastrointestinal motility in mouse models mimicking diarrhea-predominant irritable bowel syndrome symptoms

Abstract: Background The opioid and nociceptin systems play a crucial role in the maintenance of homeostasis in the gastrointestinal (GI) tract. The aim of this study was to characterize the effect of BU08070, a novel mixed MOP/NOP agonist, on mouse intestinal contractility in vitro and GI motility in vivo in physiological conditions and in animal models mimicking symptoms of irritable bowel syndrome (IBS), including diarrhea and abdominal pain. Methods The effect of BU08070 on muscle contractility in vitro was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Moreover, we observed a decrease in MPO activity after BU08070 treatment and this effect was mediated principally by MOP receptors, but not NOP receptors. These findings elegantly support the concept that the activation of opioid and NOP receptors induces anti-inflammatory response during intestinal inflammation and are in line with our earlier observations for classical and non-classical NOP and MOP receptor agonists (Sobczak et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, we observed a decrease in MPO activity after BU08070 treatment and this effect was mediated principally by MOP receptors, but not NOP receptors. These findings elegantly support the concept that the activation of opioid and NOP receptors induces anti-inflammatory response during intestinal inflammation and are in line with our earlier observations for classical and non-classical NOP and MOP receptor agonists (Sobczak et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…The attenuation of disease progression was correlated with decreased production of pro-inflammatory cytokines in the colon, including IL-1β, IL-6, and TNF-α. In contrast, in our earlier study we showed that SCH 221510, a selective NOP receptor agonist, induced anti-inflammatory response in TNBS-induced colitis in mice in a NOP receptor-reversible manner (Sobczak et al, 2014). We also observed a decrease in the relative NOP receptor mRNA expression in biopsies collected from IBD patients in comparison with healthy subjects.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, the same group has previously reported an antinociceptive effect of the same drug when orally administered in a mouse model of trinitrobenzene sulfonic acid-induced colitis. 89 In vitro afferent recordings from mouse splanchnic high-threshold nociceptors from mice with colonic inflammation we found that asimadoline (peripherally restricted selective KOR agonist) dose-dependently inhibited colonic nociceptors. Furthermore, asimadoline also dose dependently inhibited colonic nociceptors from chronic visceral hypersensitivity, an effect that was prevented by the prior application of a KOR antagonist.…”
Section: Opioid Receptorsmentioning
confidence: 83%